Slang Words Used by the Characters in Neighbors 2: Sorority Rising - Dessy Ariyanti, Ni Made (Humanis; Vol 22 No 4 (2018)DO - 10.24843/JH.2018.v22.i04.p03, 2018)
The title of this study is Slang Words Used by The Characters in Neighbors 2: Sorority Rising. This study was conducted to identify the type and to analyze the function of slang words and phrases used by the characters in the movie “Neighbors 2: Sorority Rising” . The data of this study were collected from “Neighbors 2: Sorority Rising” movie script. There were sixty-seven slang words or phrases found in the “Neighbors 2: Sorority Rising” movie script. Documentation method was used to collect the data. This study used the descriptive-qualitative method to analyze the data. There were only eighteen slang words or phrases analyzed based on the theory proposed by Allan and Burridge (2006) about type s and fun c tions of slang words. There are five types of slang found in the data. They are fresh and creative which was the most type of slang, imitative, acronym, clipping, and flippant. So, all the types of slang based on the theory were found. For the functions, there were seven functions of slang word found in the data. They are the functions of showing intimacy, addressing, forming intimate atmosphere, expressing impression, revealing anger, humiliating and initiating relax conversation. The function of showing intimacy is the most function in using slang found in the data.